2021
DOI: 10.3892/ijmm.2021.4918
|View full text |Cite
|
Sign up to set email alerts
|

Ceramide induces the apoptosis of non‑small cell lung cancer cells through the Txnip/Trx1 complex

Abstract: ceramide is a biologically active sphingomyelin that inhibits cell growth and proliferation. In previous studies, it was demonstrated that the use of lipopolysaccharides induces acid sphingomyelinases to produce ceramide, promoting lung cancer cell apoptosis; however, the specific mechanisms of this action remain unclear. Thioredoxin-interacting protein (Txnip) plays an important role in the signal transmission of redox reactions inside and outside the cell. Thus, it was hypothesized that ceramide induces apop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…A recent study has reported a novel and small molecule SphK1/2 dual inhibitor, SKI-349, with IC 50 s on primary NSCLC cells and immortalized celllines of ~5-10 μM [21]. In contrast, another recent study has reported the IC 50 of exogenous C2-Cer on NSCLC cell-lines to be ~100 μM [22]. These data together highlight the potential of our ceramide analogs as promising candidates for sphingolipid-based NSCLC therapies.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…A recent study has reported a novel and small molecule SphK1/2 dual inhibitor, SKI-349, with IC 50 s on primary NSCLC cells and immortalized celllines of ~5-10 μM [21]. In contrast, another recent study has reported the IC 50 of exogenous C2-Cer on NSCLC cell-lines to be ~100 μM [22]. These data together highlight the potential of our ceramide analogs as promising candidates for sphingolipid-based NSCLC therapies.…”
Section: Discussionmentioning
confidence: 96%
“…Our previous microarray analysis identified specific cellular genes affected by ceramide analogs, such as AURKA (Aurora A kinase) and CDCA3 (cell division cycle-associated 3), which play crucial roles in the survival of virus-associated lymphoma cells [23]. Additionally, exogenous ceramideinduced apoptosis in NSCLC cells has been linked to the Txnip/Trx1 complex [22]. The thioredoxin-interacting protein (Txnip) regulates a variety of oxidative stresses together with glutathione; it can also inhibit the exchange between the disulfide bonds of thioredoxin (Trx)1 to inhibit the reducing activity of Trx [24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…VDAC channels are a platform for the recruitment of pro-apoptotic Bak and Bax into mitochondria, leading to cytochrome c release and permeabilization of the OMM (116). Moreover, C2cermide has been found to induce apoptosis in lung adenocarcinoma cells (A549 and PC9) via regulation of the thioredoxin-interacting protein (Txnip) (117). Treatment of these cells with C2-ceramide caused an increase in the activity of caspase-3.…”
Section: Role Of Cers and Ceramides In Regulation Of Apoptosis In Cancermentioning
confidence: 99%
“…Unlike S1P, ceramide is thought to be an important secondary messenger involved in apoptosis and necrosis pathways in both normal and cancer cells [ 16 , 17 ]. In vitro studies revealed that C2 ceramide can induce apoptosis in lung cancer cells by modulating the TXNIP/Trx1 complex, inhibiting AKT and NF- κ B activity, and downregulating survivin and cyclin A2 [ 18 , 19 ]. In addition, C2 ceramide was shown to significantly affect autophagy-related factors, including SIRT1, LAMP2, and LC3, induce sustained autophagy, and increase apoptosis in non-small cell lung cancer [ 20 ].…”
Section: Sphingolipid Metabolism In Lung Cancer Progressionmentioning
confidence: 99%